Elaboración de comprimidos antigripales a base de hojas de eucalipto, limón, sauco y borraja - Honores Jaramillo, Carmen R. (2009)
The reason of this investigation work was to analyze, four plants witch action anti-gripal which are: the eucalyptus (Eucalyptus globulus), lemon (Citrus limonum), elder (Sambucus nigra), borraja (Borrago officinalis), one carries out the botanical control to all them, then you prodeede to select the material to use, obtained one carries out the drying and you crushes finely to carry out studies of rehearsals physique- chemical quantitative of general type (humidity, soluble total, ashy ashes in water, insoluble in hydrochloric acid, soluble substances) to each one of them.